Effects of Macleaya cordata extract supplementation in low-protein, low-fishmeal diets on growth, hematology, intestinal histology, and microbiota in largemouth bass (Micropterus salmoides) - Wenyuan Xu; Ruijun Zhu; Dianyu Huan; Xiaoqin Li; Xiangjun Leng (Aquaculture Reports)
The present study investigated the effects of supplementing Macleaya cordata extract (MCE) in low-fishmeal or low-protein diet on the growth performance, blood biochemical indices, intestinal morphology, and intestinal microbiota of juvenile largemouth bass. Two control diets were prepared: a low-protein diet (LP-0) containing 360 g/kg fishmeal and 460 g/kg crude protein, and a low-fishmeal diet (LF-0) containing 270 g/kg fishmeal and 500 g/kg crude protein. Then, 500 mg/kg MCE (Sangrovit) was added to the above two diets resulting in LP-500 and LF-500 diets, respectively. Juvenile largemouth bass (initial weight 21.0 ± 1.0 g) were fed the four diets for 60 days. Results showed that supplementing 500 mg/kg MCE in the low-protein diet, but not in the low-fishmeal diet, significantly increased the weight gain of largemouth bass (P < 0.05). In Aeromonashydrophila challenge test, the LP-500 group showed higher survival than the LP-0 group.In serum indices, LP-500 group presented significantly lower activity of diamine oxidase than the LP-0 group(P < 0.05). Supplementing MCE in low-fishmeal or low-protein diets significantly increased the abundance of Firmicutes in the intestinal microbiota (P < 0.05). Additionally, the expression levels of the inflammatory factors IL-10 and TGF-β1 were reduced. In summary, supplementing MCE in low-protein diet significantly improved the weight gain (P < 0.05), and MCE supplementation in low-protein or low-fishmeal diet could modulate the intestinal microbiota composition and reduce the inflammation factors expression in largemouth bass.